2016
DOI: 10.1093/brain/aww298
|View full text |Cite
|
Sign up to set email alerts
|

Myelin phagocytosis by astrocytes after myelin damage promotes lesion pathology

Abstract: Astrocytes are key players in the pathology of multiple sclerosis and can assume beneficial and detrimental roles during lesion development. The triggers and timing of the different astroglial responses in acute lesions remain unclear. Astrocytes in acute multiple sclerosis lesions have been shown previously to contain myelin debris, although its significance has not been examined. We hypothesized that myelin phagocytosis by astrocytes is an early event during lesion formation and leads to astroglial immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(181 citation statements)
references
References 38 publications
8
163
0
Order By: Relevance
“…The destructive nature of the white matter lesion was also evident from the widespread phagocytosis by gitter cells (activated microglia and blood‐derived monocytes) of abundant MBP from myelin sheath breakdown. A subset of astrocytes also showed MBP engulfment, and myelin uptake has recently been suggested to be an early response of astrocytes in diseases with myelin injury, which may also exacerbate the myelin loss …”
Section: Discussionmentioning
confidence: 97%
“…The destructive nature of the white matter lesion was also evident from the widespread phagocytosis by gitter cells (activated microglia and blood‐derived monocytes) of abundant MBP from myelin sheath breakdown. A subset of astrocytes also showed MBP engulfment, and myelin uptake has recently been suggested to be an early response of astrocytes in diseases with myelin injury, which may also exacerbate the myelin loss …”
Section: Discussionmentioning
confidence: 97%
“…IL‐17 activates and enhances the release of chemokine and pro‐inflammatory cytokines in astrocytes, which promotes the migration of CCR6 + Th17 cells to the site of inflammation (Liu et al, ; Meares, Ma, Qin, & Benveniste, ). Moreover, the presence of reactive astrocytes and axonal damage is an early event during multiple sclerosis lesion formation and lead to astrocyte immune responses (Brosnan & Raine, ; Ponath et al, ). These discoveries provide important insights into the astrocytes and Th17/IL‐17 that regulate inflammation and MS progression.…”
Section: Introductionmentioning
confidence: 99%
“…; Ponath et al . ). In addition, other authors have observed internalization of dendrimeric nanoparticles by astrocytes (Salgado et al .…”
Section: Discussionmentioning
confidence: 97%